Enhancement of Hoisting System Performance - Naji Al-azzawi, Yarub O.; Mohammed Al-Duleimi, Ra’ad K. (Al-Khwarizmi Engineering Journal, 2010)
In this paper it is required to enhance the performance of a mechanical system (here: a Hoisting System) where it is preferred to lift a different payloads with approximately the same speed of lifting and keeping at the same time the good performance, and this of course needs some intelligence of the system which will be responsible on measuring the present load and taking into account the speed and performance desired in order to achieve the requirements or the criteria. The process therefore is a Mechatronics System design which includes a measuring system, a control or automation technique, and an actuating system. The criteria built here in this research using a given Hoist system’s characteristics and parameters and changing one of these parameters by the actuator depending on load value (i.e. making a calibration with which there will be a given value of the intentional parameter at which the speed and performance reach the requirements to any load value).